SPACE REGULARITY MANIFESTATION OF THE TEMPORAL VARIATION OF SEISMIC PARAMETERS: POSSIBILITY FOR THE STRONG SEISMIC ACTIVITY ASSESSMENT - Popandopoulos, George; Baskoutas, I. (Bulletin of the Geological Society of Greece, 2010)
In the present work the detailed analysis of the space-time variation, of the seismic energy released and b-value was performed, in order to study the space regularity manifestation of the temporal variation of seismic parameters, to test the reliability of the results and to compare the obtained temporal profiles in relation to the strong earthquake activity. The study was carried out in the subduction zone along the western part of the Hellenic trench arc system. The earthquakes data, witch occurs in the five adjacent local areas in the period 1980 -2007 were used. The reliability of the results is tested positively for “internal” dubiety, against independent seismic data sets from adjacent local areas, being in common the processing method, and the properties of seismic catalogue. It was found that in the majority of the cases (23 of 32) the significant temporal variation changes, considered as anomalies, can be related to the preparation process of the strong earthquakes Ms>5.7, acting as intermediate term precursors. Based on these findings the quality index of the successful intermediate term earthquake predictions reach up to 71.9%. It is observed that the temporal variation of the seismic energy released anomalies were time shifted in respect to the central areas, toward to N-NE and S-SE direction. Moreover it is found that the strong earthquakes occurrence also shows immigration, in respect to the central areas, along the concatenation of the adjacent local areas. These two observations may reveal the formation of a tectonic wave, in the broader area south of Zakynthos Island, Its velocity was estimated to be as 100 to 150 km/year